(untitled) (Konturen, 2020)
The rise of anti-immigrant sentiment and right-wing extremism in Sweden in the wake of growing migration has affected Sweden’s global reputation as a model progressive welfare state that prioritizes human rights and generously extends citizenship, welfare, and labor rights to migrants and asylum seekers. In Jonas Hassen Khemiri’s Allt jag inte minns [Everything I Don’t Remember] (2015), xenophobia, Islamophobia, and racialized heteronormativity appear in the unlikely form of Vandad, a hypermasculine Muslim immigrant who has secretly fallen in love with another Swedish Arab man. This study involves a narratological analysis of how internalized racism inspires the novel’s narrator of color to produce figurative narrative acts of internal colonialism—that is, violent narrative acts, made possible by the effects of racism, against other non-white characters in the story. The essay additionally explores how the objectification of non-white women’s bodies and acts of misogynoir, the anti-Black misogyny that Black women experience, by queer men of color in the text operate as secondhand technologies of oppression manufactured by the political discourse of the extreme right. The essay concludes with a critique of the far right’s exploitation of collective cultural memory to mass-produce white nationalism in the guise of tradition and the implications this has for non-white Swedes and migrants in Sweden.